A solitude of wolverines : a novel of suspense - Henderson, Alice (Henderson, Alice. Alex Carter, 2020)
"While studying wolverines on a wildlife sanctuary in Montana, biologist Alex Carter is run off the road and threatened by locals determined to force her off the land. Undeterred in her mission to help save this threatened species, Alex tracks wolverines on foot and by cameras positioned in remote regions of the preserve. But when she reviews the photos, she discovers disturbing images of an animal of a different kind: a severely injured man seemingly lost and wandering in the wilds. After searches for the unknown man come up empty, local law enforcement is strangely set on dismissing the case altogether, raising Alex's suspicions. Then another invasive predator trespasses onto the preserve. The hunter turns out to be another human - and the prey is the wildlife biologist herself. Alex realizes too late that she has seen too much - she's stumbled onto a far-reaching illegal operation and now has become the biggest threat. In this wild and dangerous landscape, Alex's life depends on staying one step ahead - using all she knows about the animal world and what it takes to win the brutal battle for survival."--Publisher description.